A Companion to English Renaissance Literature and Culture. - Hattaway, Michael (Blackwell companions to literature and culture., 2007)
This is a one volume, up-to-date collection of more than fifty wide-ranging essays which will inspire and guide students of the Renaissance and provide course leaders with a substantial and helpful frame of reference.:.; Provides new perspectives on established texts.; Orientates the new student, while providing advanced students with current and new directions.; Pioneered by leading scholars.; Occupies a unique niche in Renaissance studies.; Illustrated with 12 single-page black and white prints.